Effects of different foods and cooking methods on the gut microbiota: an in vitro approach - Lerma-Aguilera, Alberto M.; Pérez-Burillo, Sergio; Navajas-Porras, Beatriz; León, E. Daniel; Ruíz-Pérez, Sonia; Pastoriza, Silvia; Jiménez-Hernández, Nuria; Cämmerer, Bettina-Maria; Rufián-Henares, José Ángel; Gosalbes, María José; Francino, M. Pilar (Frontiers in Microbiology, 2024)
To support personalized diets targeting the gut microbiota, we employed an in vitro digestionfermentation model and 16S rRNA gene sequencing to analyze the microbiota growing on representative foods of the Mediterranean and Western diets, as well as the influence of cooking methods. Plant-and animal-derived foods had significantly different impacts on the abundances of 2 This is a provisional file, not the final typeset article bacterial taxa. Animal and vegetable fats, fish and dairy products led to increases in many taxa, mainly within the Lachnospiraceae. In particular, fats favored increases in the beneficial bacteria Faecalibacterium, Blautia and Roseburia. However, butter, as well as gouda cheese and fish, also resulted in the increase of Lachnoclostridium, associated to several diseases. Frying and boiling produced the most distinct effects on the microbiota, with members of the Lachnospiraceae and Ruminococcaceae responding the most to the cooking method employed. Nevertheless, cooking effects were highly individualized and food-dependent, challenging the investigation of their role in personalized diets.